2022
DOI: 10.3390/nu14235131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Determinants, and Consumer Stance towards Dietary Supplements According to Sex in a Large Greek Sample: A Cross-Sectional Study

Abstract: A stratified random sampling technique was used in order to explore the prevalence of and the factors influencing dietary supplement (DS) use and the consumer stance towards DS by Greeks (n = 28,491, ≥15 years) according to sex. Additionally, we performed a Pearson’s chi-square to test within DS users for the dependence between sex and the examined factors, and binary logistic regression to create predictive DS user profiles. A history of DS use accounted for 55.5% and was more prevalent in women (58.4% vs. 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…This finding is similar to the study reported by Keshavarz et al, 29 which found that men (38%) and women (53%) in Canada used dietary supplements. This prevalence is lower compared to studies reported by Mishra et al 13 which found more than half (57.6%) of adults aged 20 years and above in the United States used any dietary supplements, and Soukiasian et al 30 which reported that 55.5% of Greek adult consumers accounted for the history of dietary supplement use. However, this study's finding is higher than the study reported by Dlamini et al 19 which found that only 14.4% of the adult population in urban Kenya had taken dietary supplements in the past 12 months.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is similar to the study reported by Keshavarz et al, 29 which found that men (38%) and women (53%) in Canada used dietary supplements. This prevalence is lower compared to studies reported by Mishra et al 13 which found more than half (57.6%) of adults aged 20 years and above in the United States used any dietary supplements, and Soukiasian et al 30 which reported that 55.5% of Greek adult consumers accounted for the history of dietary supplement use. However, this study's finding is higher than the study reported by Dlamini et al 19 which found that only 14.4% of the adult population in urban Kenya had taken dietary supplements in the past 12 months.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite that the “improvement of the immune system/defense system” was the main reason for the use of PFS in children (31%), men (17%), and women (19%), the following motives were different among the three subgroups, namely, flu/cold (12%), energy (9%), relaxing (6%), and general health (6%) for children, energy (11%), heart/blood circulation (7%), general health (6%), and digestive function (6%) for men, and urinary tract (8%), energy (8%), digestive function (7%), and other (7%) for women. More recently, a cross-sectional study based on in-person questionnaires collected from 2018 to 2019 among the Greek population, with a final sample size of 28,491 respondents aged more than 15 years old, demonstrated that 55.5% used dietary supplements, with vitamins (77.3%) being the most used, followed by minerals (54.4%) and herbs or extracts (50.3%) [ 49 ]. The most common reason for using food supplements was the improvement of physical condition and treatment of nutrient deficiencies for both men and women, followed by the treatment or prevention of pathological conditions, such as anemias and osteoporosis in the group of women (31.3%) or the increase of muscle mass (31.0%) and sports performance (26.8%) in the case of men.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements are presently utilized more frequently than ever before due to their efficacy and safety in improving general health [8][9][10]. The European Union, the United States [11][12][13][14], and the nations of the Gulf Cooperation Council [15,16] all make extensive use of DSs. Moreover, nutritional supplements are presently regarded as one of the most significant trends in the healthcare industry, which has a significant impact on the global economy [17].…”
Section: Introductionmentioning
confidence: 99%